Al-Dalālāt al-Naḥwīyah li-Ḥarf al-Jarr “Min” fī Matn al-Ghāyah wal-al-Taqrīb li-Abī Shujāʿ al-Iṣfahānī: Dirāsah Taḥlīlīyah fī al-Siyāq al-Fiqhī - Ardhiani, Aldia Rahma; El Farruq, Mohammed Dzaky (Alsina : Journal of Arabic Studies, 2024)
This study analyzes all instances of the preposition “min” in Matn al-Ghāyah wal-Taqrīb by Abū Shujāʿ al-Iṣfahānī, with the aid of an Indonesian translation to facilitate tracing. The method employed is library research with a descriptive qualitative approach. The analysis focuses on identifying the meaning of the preposition “min” based on its syntactic and semantic contexts in the text. A total of 177 occurrences of “min” were found, reflecting eleven primary meanings. The most dominant meaning is bayān al-jins (28.8%), typically in sacrificial animals, zakat, and wives’ maintenance discussions. This meaning is followed by zā’idah (22.0%), often found in emphatic contexts or following a negative element, and tabʿīḍ (20.9%), related to partition or part of a category. The meaning ibtidāʾ al-ghāyah (13.0%) also appears in zakat, pilgrimage, and expiation topics. Other meanings, such as al-mujāwazah, taʿlīl, and several minor meanings, were found in smaller numbers. These results indicate that the distribution of meanings is uneven and influenced by fiqh themes and the normative objectives of the text. Studying grammatical structure and semantic function within legal contexts analyzes four primary meanings deeply. These findings confirm that using the preposition “min” in fiqh texts is systematic and reflects a linguistic strategy aligned with the pattern of Islamic legal formulation.